Pengendalian Hama Ramah Lingkungan di Wilayah Tanjung Selor - Muh. Adiwena; Abdul Rahim; Muh. Guruh Aris Munandar (Universitas Mathla'ul Anwar Banten, 2022)
ECO-FRIENDLY PEST MANAGEMENT İN TANJUNG SELOR REGİON. Pest control in the most parts of the Republic of Indonesia still relies on the application of synthetic chemical insecticides, including the Tanjung Selor area. Tanjung Selor is the administrative center or capital of the province of North Kalimantan. This sub-district located in Bulungan Regency, North Kalimantan Province, Indonesia with the majority of the population working as farmers. The unwise use of synthetic chemical insecticides by farmers has a negative impact on many aspects. Therefore, it is necessary to socialize about environmentally friendly pest control. This activity begins with a preliminary survey in order to determine the respondents and the efficiency of the implementation of the next activity. After that, the activities were socialization and ended with an evaluation to determine the effect of the activities. The activities have a positive influence on the knowledge and actions of farmers on environmentally friendly pest control. Prior to the activity, only 27% of farmers knew about it and 10% carried out environmentally friendly pest control. However, three months after the activity, these two figures increased to 40% and 15%.